Therapeutic Journey and Recent Advances in the Synthesis of Coumarin Derivatives - Sinha, Shweta; Singh, Kuldeep; Ved, Akash; Hasan, Syed M.; Mujeeb, Samar (Mini Reviews in Medicinal Chemistry, 2022)
Background: Coumarin is an oxygen-containing compound in medicinal chemistry. Coumarin plays an important role in both natural systems like plants and synthetic medicinal applications as drug molecules. Many structurally different coumarin compounds have been found to possess a wide range of similarities with the vital molecular targets in terms of their pharmacological action and small modifications in their structures, resulting in significant changes in their biological activities. Objective: This review provides detailed information regarding the studies focused on the recent advances in various pharmacological aspects of coumarins. Methods: Various oxygen-containing heterocyclic compounds represent remarkable biological significance. The fused aromatic oxygen-heterocyclic nucleus can change its electron density, thus altering the chemical, physical and biological properties, respectively, due to its multiple binding modes with the receptors, which play a crucial role in the pharmacological screening of drugs. Several heterocyclic compounds have been synthesized which have their nuclei derived from various plants and animals. In coumarins, the benzene ring is fused with a pyrone nucleus which provides stability to the nucleus. Coumarins have shown a wide range of pharmacological activities, such as anti-tumor, anticoagulant, anti-inflammatory, anti-oxidant, antiviral, antimalarial, anti-HIV, antimicrobial, etc. Results: Reactive oxygen species, like superoxide anion, hydroxyl radical, and hydrogen peroxide, are a type of unstable molecule containing oxygen, which reacts with other molecules in the cell during metabolism; however, when the number of reactive oxygen species increases, it may lead to cytotoxicity, thereby damaging the biological macromolecules. Hydroxyl Radical (OH) is a strong oxidizing agent and it is responsible for the cytotoxicity caused by oxygen in different plants, animals, and other microbes. Coumarin is the oldest and effective compound having antimicrobial, anti-inflammatory, antioxidant, antidepressant, analgesic, anticonvulsant activities, etc. Naturally existing coumarin compounds act against SARS-CoV-2 by preventing viral replication and targeting the active site against the Mpro target protein. Conclusion: This review highlights the different biological activities of coumarin derivatives. In this review, we provide an updated summary of the researches which are related to recent advances in biological activities of coumarins analogs and their most recent activities against COVID -19. Natural compounds act as a rich resource for novel drug development against various SARS-CoV-2 viral strains and viruses, like herpes simplex virus, influenza virus, human immunodeficiency virus, hepatitis B and C viruses, middle east respiratory syndrome, and severe acute respiratory syndrome.
Keywords: antimicrobial